2012
DOI: 10.1002/joc.3562
|View full text |Cite
|
Sign up to set email alerts
|

Temporal–spatial distribution of the predictability limit of monthly sea surface temperature in the global oceans

Abstract: ABSTRACT:To examine atmospheric and oceanic predictability based on nonlinear error growth dynamics, the authors introduced recently a new method using the nonlinear local Lyapunov exponent (NLLE). In this study, the NLLE method is employed to investigate the temporal-spatial distribution of the limit of sea surface temperature (SST) predictability, based on reanalysis monthly SST data. The results show that the annual mean limit of SST predictability is the greatest in the tropical central-eastern Pacific (>8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 76 publications
4
33
0
Order By: Relevance
“…Slab models provide as much predictability and forecast skill (∼1 y) as coupled models, which is surprising because slab models do not contain the oceanic Rossby and Kelvin waves associated with ENSO mechanisms. Also, the prediction skill of ENSO in current dynamical and statistical models is less than a year (39)(40)(41). Subsequent predictable components (i.e., components 4, 5, and 6) in slab and coupled models show similar spatial structure, predictability, and skill, but these are not shown, for brevity.…”
Section: Resultsmentioning
confidence: 97%
“…Slab models provide as much predictability and forecast skill (∼1 y) as coupled models, which is surprising because slab models do not contain the oceanic Rossby and Kelvin waves associated with ENSO mechanisms. Also, the prediction skill of ENSO in current dynamical and statistical models is less than a year (39)(40)(41). Subsequent predictable components (i.e., components 4, 5, and 6) in slab and coupled models show similar spatial structure, predictability, and skill, but these are not shown, for brevity.…”
Section: Resultsmentioning
confidence: 97%
“…Generally, exponential distribution (Equation (2)) is used to model drought duration, while gamma distribution (Equation (3)) fits drought severity. However, in this study the entropy-based distribution was used to model the marginal distributions of both variables (see Equations (11) and (12)), with the empirical distribution being used for comparison. For the evenly selected stations in Figure 1, the theoretical cumulative distribution, entropy-based cumulative distribution and empirical cumulative distribution are shown in Figures 5 and 6.…”
Section: Drought Characteristic and Distribution Testmentioning
confidence: 99%
“…To date, many drought indices have been proposed for quantifying, monitoring and analyzing droughts [4,5], but the drought problem is a complex one involving a great many factors [6][7][8][9][10][11][12]. There is no unified index because of the complexity of the physical processes involved; however, many studies have shown that the intensity, duration and spatial extent are the main characteristics of droughts [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results of Ding and Li (2007) show that, compared with a linear local or finitetime Lyapunov exponent, the NLLE is more appropriate for the quantitative determination of the predictability limit of a chaotic system. Based on observational or reanalysis data, the NLLE method has been used to investigate the atmospheric predictability at various timescales (Ding et al, , 2010(Ding et al, , 2016Li and Ding, 2008, 2013.…”
Section: Introductionmentioning
confidence: 99%